Deciphering the appropriateness of defaults: the need for domain-specific evidence. Issue 12 (23rd November 2012) - Quill, Caroline Mayberry; Halpern, Scott
Abstract : In this issue of The Journal of Medical Ethics, xxx and colleagues report a randomized trial of the influence of default options on delivery room management of an extremely premature infant. They report that among respondents to the hypothetical vignette, those who received the resuscitation default were significantly more likely to choose resuscitation compared with those who were told that the default was comfort care. While the results warrant attention and further investigation, several methodological shortcomings limit the conclusions that can be drawn from this study.